KONSEP RESILIENSI IBU TUNGGAL PADA KOMUNITAS SINGLE MOMS INDONESIA - Darmaningrum, Khaerunnisa Tri (Kafa`ah: Journal of Gender Studies, 2023)
This study explains how single mothers in the Indonesian Single Moms community have problems both internally and externally. The external problem they often experience is the labeling of the status of single mothers in society. Apart from these external problems, single mothers also have internal problems where she experiences a change in identity which often affects their mental health as single mothers who have the responsibility to support their children. This study uses case studies to obtain more in-depth data on cases of single mothers in the Indonesian Single Moms community. The primary sources are 9 single mothers with 3 backgrounds which make them a single mother, the first because of the death of her second husband due to divorce and the third because she decided not to marry. Based on the research data, it can be explained that the research results are that single mothers have problems that are not easy.